Weeds and weed management in Malaysian agriculture. - Mohamad, Rosli (1989)
The manace of weeds and the importance of weed control/management are well recognized in the plantation crops as well as the smallholding farms. The problem receives special attention in crop management practices. This paper reviews briefly the impact of weed infestation in crops of agricultural importance in Malaysia. Weed distribution and importance, and general weed control/management methods are discussed in accordance with the major crops. Weeds can retard crop growth, reduce yield and interfere with farm operations. Climatic condition, crops and cropping systems determine the weed species distribution. Cultural, mechanical, biological and chemical methods of weed control are practiced.